Maori identity and "political arithmetick" : the dynamics of reporting ethnicity - Kukutai, Tahu (2022)
Thesis (M. Soc.Sc. Demography)--University of Waikato, 2001. Includes bibliographical references (leaves 193-203)
Keywords: crown policy; ethnic identity; ethnicity

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination

Chapter 9: Indigenous Data Sovereignty: Implications for Data Journalism - Kukutai, Tahu; Walter, Maggie (The Data Journalism Handbook: Towards a Critical Data Practice, 2021)
Keywords: indigenous data sovereignty

New normal - Same inequities or engaged Te Tiriti partnership? - Kukutai, Tahu; McIntosh, Tracey; Moewaka Barnes, Helen; McCreanor, Tim (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; mātauranga māori; tiriti o waitangi/treaty of waitangi; treaty partnership; treaty-based relationships

Recession hits Māori and Pasifika harder. They must be part of planning New Zealand's COVID-19 recovery - Moewaka Barnes, Helen; Kukutai, Tahu; McCreanor, Tim; Mcintosh, Tracey (The Conversation, 2020)
Māori knowledge, memory and cultural strength will only enhance New Zealand’s economic recovery planning – if they are listened to.
Keywords: covid-19; crown policy; discrimination; treaty obligations

Indigenous Peoples, Data, and the Coloniality of Surveillance - Cormack, Donna; Kukutai, Tahu (New Perspectives in Critical Data Studies: The Ambivalences of Data Power, 2022)
In Aotearoa New Zealand (Aotearoa NZ), Māori (the Indigenous peoples of New Zealand) have long been objects of surveillance by state institutions and agents. State representations have centred on constructions of difference and deviance, on understandings of Indigenous peoples as dangerous, and on the management of Indigenous resistance to colonialism. This chapter considers how contemporary state surveillance practices in Aotearoa NZ, enabled by the expanded use of big data and linked government datasets, function to regulate and manage Māori. Through this lens, we explore continuities of current data practices for Indigenous peoples with the racialised logics and social orders set in place as part of global systems of imperialism and colonialism. Recognising that resistance has always been a part of Indigenous responses to colonialism, we also explore how Māori Data Sovereignty (MDSov), as part of broader Indigenous Data Sovereignty (IDS) movements globally, provides opportunities to counter and disrupt prevailing data relations and to imagine alternative futures.
Keywords: colonisation; data; data sovereignty; indigenous data sovereignty; surveillance

Pandemic Paternalism: A Reflection on Indigenous Data from Aotearoa - Kukutai, Tahu; Cormack, Donna (COVID 19 FROM THE MARGINS: PANDEMIC INVISIBILITIES, POLICIES AND RESISTANCE IN THE DATAFIED SOCIETY, 2021)
Keywords: covid-19

Beyond the “Abyssal Line”: Knowledge, Power, and Justice in a Datafied World - Cormack, Donna; King, Paula (The Oxford Handbook of Indigenous Sociology, 2021)
Colonization fundamentally disrupted Indigenous knowledge systems, establishing epistemic hierarchies that privilege Eurocentric colonial epistemologies and methodologies. In this chapter, the authors explore how epistemic hierarchies are (re)produced in the current context of “big data” and datafication, in particular for mokopuna Māori in the nation-state known as New Zealand (NZ). (We use the concept of “mokopuna Māori” to refer to and position Māori babies, children, and young people within the Māori world as the sacred reflection of our ancestors and a blueprint for future generations.) The chapter then considers the possibilities for Indigenous epistemic justice in the “zone of nonbeing” or beyond the “abyssal line.”
Keywords: colonial methodology; colonisation; data; data sovereignty; heirarchy; kaupapa māori; methodology

Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.
Keywords: colonisation; covid-19; data; data sovereignty; inequity; racism; self-determination

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics